The Validity of the School Assessment in the Craft Subject - Antti Hilmola; Manne Kallio (Techne Series: Research in Sloyd Education and Craft Science A, 2016)
In this research project, the validity of the school assessment is examined in the craft subject in Finland’s basic education. The criteria for the school assessment are based on the Finnish Na-tional Core Curriculum (FNCC) in which the idea of the Entire Craft (EC) is highlighted. How-ever, the discussion as to whether or not the school practice is based on the idea of EC, or whether the teachers are still focused on the technical details of products in reflecting on the pupils’ tool-handling skills, is still an ongoing debate. Learner-centred learning is implicated in EC since the pupils are expected to set goals for the implementation of their own ideating, plan-ning and constructing. And, finally, in such a process, the self-reflection of the implemented out-comes against the goals will take place.  Altogether 73 craft teachers from 59 upper level schools participated in this research project. The pupils’ (N = 982) success was assessed during an EC period using the indicator validated by the previous nation-wide evaluation by the Finn-ish National Board of Education (FNBE). Since the valid school assessment was expected to reflect the success in the Entire Craft Assessment Period (ECAP), the outcomes were assessed against the criteria of the FNCC and compared to the pupils’ school scores. The data was ana-lysed using the Linear Regression Analysis (Enter Method). The central observation was that the pupils’ success in the criteria of the EC do not reflect the 7th grade school scores, in all re-spects. Moreover, the pupils’ success does not reflect the 6th grade school scores. The instruc-tions and supplementary education of the FNCC criteria are needed for craft teachers, especial-ly for class teachers at the lower level. In Finland, also the craft subject is taught by the class teachers at the lower level while, at the upper level, the subject teachers take their place. Ac-cording to the new FNCC, the number of class lessons will be diminished at the upper level and increased at the lower level. This might challenge the assessment in the craft subject in basic education. Special attention should be paid to the school assessment in 2016, at the latest, when the new National Core Curriculum comes into force.